2015
DOI: 10.1007/s11269-015-1116-6
|View full text |Cite
|
Sign up to set email alerts
|

Semi-analytical Solutions of Multiprocessing Non-equilibrium Transport Equations with Linear and Exponential Distance-Dependent Dispersivity

Abstract: In this paper, a semi-analytical solution of multiprocess non-equilibrium (MPNE) transport equations with linear and exponential distance-dependent dispersivity is developed. The model has been used to simulate the laboratory experimental data of chloride and fluoride solutes through a 15 m long heterogeneous soil column. It is observed that a better fit to the observed breakthrough curves is obtained, when the mass transfer between advective and non-advection region is considered. It is also observed that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Brusseau and Srivastava (1997) reported several factors affecting the transport of organic solutes, including physical and chemical heterogeneity and nonlinear and rate‐limited sorption. Several conceptual models have been developed to analyze the fate of solutes in heterogeneous porous media by considering nonequilibrium, multi‐rate mass transfer, and/or non‐Fickian transport behavior (Brusseau et al., 1989; Haggerty & Gorelick, 1995; Pot et al., 2005; Selim et al., 1999; Sharma et al., 2015, 2016; Srivastava & Brusseau, 1996; van Genuchten & Wierenga, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Brusseau and Srivastava (1997) reported several factors affecting the transport of organic solutes, including physical and chemical heterogeneity and nonlinear and rate‐limited sorption. Several conceptual models have been developed to analyze the fate of solutes in heterogeneous porous media by considering nonequilibrium, multi‐rate mass transfer, and/or non‐Fickian transport behavior (Brusseau et al., 1989; Haggerty & Gorelick, 1995; Pot et al., 2005; Selim et al., 1999; Sharma et al., 2015, 2016; Srivastava & Brusseau, 1996; van Genuchten & Wierenga, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of laboratory and field experiments have shown that ADE could not capture the early arrival and long tailing of breakthrough curves (BTCs) [4,5]. Dispersivity is widely thought to be related to scale dependence, and the scale-dependent dispersivity is largely due to the heterogeneity of porous media at different scales [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical solutions of one-dimensional solute transport problems, subject to different initial and boundary conditions, infinite and the semi-finite domain have been reported by many researchers (Ogata & Banks 1961;Neville et al 2000;Gao et al 2010;Joshi et al 2012;Leij et al 2012;Sharma et al 2015;Masciopinto & Passarella 2018). Solutions of two-, three-dimensional deterministic ADE's have been investigated in numerous studies and are still being actively studied (Freeze & Cherry 1979;Latinopoulos et al 1988;Batu 1989;Leij et al 1991, Batu 1993Leij et al 1993;Serrano 1995).…”
Section: Introductionmentioning
confidence: 99%